2007
DOI: 10.1007/s10802-007-9185-5
|View full text |Cite
|
Sign up to set email alerts
|

Inattention/Overactivity Following Early Severe Institutional Deprivation: Presentation and Associations in Early Adolescence

Abstract: The current study examined the persistence and phenotypic presentation of inattention/overactivity (I/O) into early adolescence, in a sample of institution reared (IR) children adopted from Romania before the age of 43 months. Total sample comprised 144 IR and 21 non-IR Romanian adoptees, and a comparison group of 52 within-UK adoptees, assessed at ages 6 and 11 years. I/O was rated using Rutter Scales completed by parents and teachers. I/O continued to be strongly associated with institutional deprivation, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
172
0
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(203 citation statements)
references
References 53 publications
(64 reference statements)
21
172
0
10
Order By: Relevance
“…It proved surprising, however, that these institutional features did not predict ADHD symptoms, especially given results of related investigations [8,9]. We are not the first to fail to document such seemingly anticipated associations, however, thereby calling attention to methodological differences across inquiries that could account for variation in results.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…It proved surprising, however, that these institutional features did not predict ADHD symptoms, especially given results of related investigations [8,9]. We are not the first to fail to document such seemingly anticipated associations, however, thereby calling attention to methodological differences across inquiries that could account for variation in results.…”
Section: Discussionmentioning
confidence: 75%
“…We are not the first to fail to document such seemingly anticipated associations, however, thereby calling attention to methodological differences across inquiries that could account for variation in results. Recall that in our own and in Zeanah and colleagues' [6] work, the focus was on children still institutionalized, whereas other research focused on previously institutionalized children, living with their adoptive families [8,9]. Another factor to consider in entertaining reasons for divergent results across studies is that the absence of an effect of duration of deprivation on ADHD may be attributable to the fact that all children from the current study were institutionalized for no less than 6 months and this was by no means the case in other work.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous laboratory studies with older PI children have shown reduced performance on each of these components: cognitive flexibility (11), working memory performance (11,12,15), and inhibitory control (13,15,31). Additionally, there are extensive reports that PI children show attention deficits and hyperactivity symptoms that persist into adolescence (32,33), which could signal long-term difficulties with EF.…”
Section: Ef In Postinstitutionalized Childrenmentioning
confidence: 99%